(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The spread of Islam in the Kazakh community, leading a nomadic way of life was associated with a complex historical process, which lasted for several centuries. On the territory of the spread of Islam, Islamic education system was introduced gradually. This process lasted until the beginning of a new learning stage. This article is a brief historical analysis from the theological point of view on the formation of a complex system of madrassas to Islamic science. Key words: madrasah, Islam, religion, culture, School.